2018
DOI: 10.1093/neuros/nyy156
|View full text |Cite
|
Sign up to set email alerts
|

Study Protocol: Early Stereotactic Gamma Knife Radiosurgery to Residual Tumor After Surgery of Newly Diagnosed Glioblastoma (Gamma-GBM)

Abstract: Early postoperative SRS to areas of residual tumor could bridge the therapeutic gap between surgery and adjuvant therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Phase II trials are currently underway, evaluating the efficacy of PBT as a frontline treatment compared to standard dose radiotherapy with TMZ. The delivery of high dose radiation to the tumor can also be achieved via Gamma Knife Radiosurgery, which has been utilized for the treatment of recurrent GBM [ 54 , 55 , 56 ]. It has been observed that significant radiation-induced edema occurs in patients who receive high radiation doses; however, these adverse side effects were reduced, and patient survival prolonged when combined with bevacizumab [ 57 , 58 ].…”
Section: Therapeutic Strategies For Glioblastomamentioning
confidence: 99%
“…Phase II trials are currently underway, evaluating the efficacy of PBT as a frontline treatment compared to standard dose radiotherapy with TMZ. The delivery of high dose radiation to the tumor can also be achieved via Gamma Knife Radiosurgery, which has been utilized for the treatment of recurrent GBM [ 54 , 55 , 56 ]. It has been observed that significant radiation-induced edema occurs in patients who receive high radiation doses; however, these adverse side effects were reduced, and patient survival prolonged when combined with bevacizumab [ 57 , 58 ].…”
Section: Therapeutic Strategies For Glioblastomamentioning
confidence: 99%
“…Unlike advancing age, the EOR plays an important role in improving survival. The purpose of the surgical resection is to remove the tumor as much as possible, alleviating the mass effect, to obtain brain tissue for the analysis of the pathology [42]. However, in 90% of cases, the tumor recurrence can occur within a 2-cm margin of the primary site [43].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, early postoperative EBRT in the form of SRS has not demonstrated conclusive efficacy. A future trial will test SRS ≤ 48 h postoperatively for residual tumour [ 80 ].…”
Section: Clinical Interventionsmentioning
confidence: 99%